Mindful leadership coaching journeys into the interior - Kets de Vries, Manfred F. R. (Palgrave Macmillan, 2014)
Mindful Leadership Coaching takes an in-depth look at the coaching processes. The insights provided here will help coaches and executives to use frameworks for transforming attitudes, beliefs, and behaviors. It advises on how the best leadership coaches help their executive clients create significant personal and professional change.